Ways to reduce road traffic load of city transport networks - Дульфан, Сергій Борисович; Лобашов, Олексій Олегович (Technology audit and production reserves, 2013)
At the present time, there is a problem of choosing the most effective, scientifically grounded directions of activity to reduce the road traffic load of city transport networks. The paper gives the analysis and the developed classification of modern ways on the reduction of the road traffic load of city transport networks. As a result, the measures most relevant for modern conditions − organization of park-and-ride facilities in the peripheral areas of cities and construction of parallel highways were chosen. The structural diagram of the developed method of studying the efficiency of selected measures to reduce the road traffic load of transport networks is given. The method is based on the modeling of traffic flows using a mathematical model of the transport network load. The use of the given method allows determining the parameters of dependency of the level of traffic load of the transport network on the characteristics of applied measures and, therefore, establishing the appropriateness of their use.